The Influence of Brand Image, Price, and Promotion on the Purchasing Decision of White Koffie Civet Coffee in the South Jakarta Area - Muhammad Michelle Rizki Byhaqi; Subur Karyatun; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to analyze the effect of Brand Image, Price, and Promotion on Purchase Decisions in the South Jakarta Region. This study uses primary data and secondary data with the method of collecting data through questionnaires distributed to 100 respondents. Data analysis technique using multiple linear regression analysis. From the results of multiple linear regression analysis shows that the variable Brand Image has a positive but not significant effect, Price has a positive and significant effect, and Promotion has a positive and significant effect on Purchase Decisions. Based on this research, it is hoped that the community of instant ground coffee lovers in the South Jakarta area can be interested in buying Kopi Luwak White Koffie because of the Brand Image, Price, and Promotion provided by Kopi Luwak White Koffie.